Inovação em marketing nos shopping centers: um estudo de aplicações de tecnologia em ações promocionais em dois shopping centers brasileiros - Silva, Rayssa Belke (2017)
Purpose - The objective of this work is to identify and analyze the role of innovation, in particular the use of information technology, in the marketing actions of the shopping malls and to evaluate its strategic role in the differentiation of the enterprises given the high competition of the market. Methodology - The methodology used in this research had qualitative approach with an exploratory character to obtain and analyze the data. It should be emphasized that the data were obtained through individual interviews based on a semi-structured questionnaire. In addition, a documentary survey was carried out by means of the analysis in the financial reports of the company. Findings - The final considerations demonstrate that innovation as a strategy of competitive advantage is still far below its potential in the two malls research objects. The shopping center model itself, in the cases examined, continues with a traditional bias and with structural gaps that are directly related to its difficulty adapting to technological advances and modifying its business strategy. Limitations - The main limitation of the research is the generalization from the analysis of two cases of application of information technology in marketing actions in Brazilian shopping centers. In addition, the innovations studied have specific characteristics, which could be characterized as experiments rather than current practices. Practical contributions - From these results, one can see that there is a broad field of development and solidification of marketing actions that involve IT innovation in shopping centers. However, in order to be successful, it is necessary to be preceded by some pre-requirements, such as improvement in the relationship between shopkeepers and administration, formalization of marketing planning, training of mall marketing teams and diversification of actions. Originality - This is one of the few study studies that evaluates the application of technology in promotional actions in Brazilian shopping malls